Inventory of Interpersonal Problems-32 (IIP-32): Psychometric Properties in Adolescents from Argentina - Areas, Malenka Alejandra (2022)
The Inventory of Interpersonal Problems (IIP) is a widely studied instrument in themental health field.  While there havebeen some applications of this tool in adolescents, the majority of researchhas focused on the adult population. This study aims to examine thepsychometric properties of the Inventory of Interpersonal Problems-32 (IIP-32)specifically in Argentinian adolescents. A total of 557 participants completedthe IIP-32 alongside an additional assessment of interpersonal traits. Toevaluate reliability, we analyzed internal consistency and item homogeneity. Weanalyzed the construct validity of IIP-32 through confirmatory factor analysisand the concurrent validity through correlations between the IIP-32 and othermeasures of interpersonal traits. The findings of this study indicate adequateinternal consistency and homogeneity of the items, as well as construct,concurrent and criterion validity. Overall, the results of this paper establishthe IIP-32 as a reliable and valid instrument with significant clinicalimplications for assessing interpersonal difficulties in adolescents from Argentina.